Safe harbors for patent infringers: sequential innovation under incomplete patent protection - Alexandra Zaby (ZBW - Leibniz Information Centre for Economics, 2020)
From the viewpoint of an innovator a patent is a tradeoff between the right to exclude others from using the patented matter versus the requirement to disclose it. Given the sequential nature of many innovations, patent induced technology diffusion can spur technological progress. However, second innovators face the risk of being sued for infringement of the original patent. Incomplete patent protection reduces the risk of such infringement: either a narrow 'leading breadth' of the patent or the intentional containment of patent protection by a "research use" or "Bolar exemption" provide "safe harbors" for second innovators. This paper investigates how incomplete patent protection affects the propensity to patent of the initial inventor on the one hand and overall innovation incentives on the other hand. We find that incomplete patent protection can positively affect overall innovation incentives while maintaining the advantageousness of patent protection over secrecy. However, if second innovators face a very low risk of being punished for patent infringement, the propensity to patent decreases.
Keywords: O31; O24; L24; D21; 330; sequential innovation; research use exemption; patenting decision; patent race; incomplete patent protection